Strategi Social CRM Dalam Menangani Keluhan Pelanggan Pada Instagram Pos Indonesia - Risma Cahyani; Anisa Diniati (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Every day, many customers submit complaints through the comment section on Pos Indonesia's main Instagram account (@posindonesia.ig). This study aims to understand how Pos Indonesia designs its Social CRM strategy to address customer complaints on the Instagram social media platform @posindonesia.ig. The theory employed in this research is the Social Media SOME model (Share, Optimize, Manage, Engage) developed by Luttrell (2018). A qualitative approach with descriptive research is utilized in this study. Data collection methods involve in-depth interviews, observation, and document analysis. The findings of this research reveal that the Social CRM Strategy implemented by Pos Indonesia's internal communication and contact center includes four main activities: (1) Share, where internal communication strives to reduce negative sentiment by paying attention to the content liked by followers, (2) Optimize, where internal communication focuses on educational content presented in a socializing format, (3) Manage, where internal communication monitors social media content to assess the level of impressions and sentiments from followers, and (4) Engage, where internal communication involves internal buzzers to provide positive comments with the hope that customers planning to express negative complaints will change their minds.